STRATEGI PENGUSAHA KHAS PALEMBANG DALAM MEMPERTAHANKAN KELANGSUNGAN HIDUP PERUSAHAAN DAN FAKTOR-FAKTOR YANG MEMPENGARUHINYA - Sri Artati Waluyati; Dwi Hasmidyani (Jurnal PROFIT: Kajian Pendidikan Ekonomi dan Ilmu Ekonomi, 2014)
This Research Is Entitled The Strategy of Palembang's Entrepreneurial Entrepreneurship and Maintaining the Sustainability of Its Business and Its Affecting Factors. The location of the research is focused on the craftsmen center of Palembang, which is located in the road of Faqih jalaludin 19 Ilir Palembang. This research uses qualitative descriptive approach. The population in this study is a typical Palembang carving entrepreneurs, amounting to 12 entrepreneurs. Data collection techniques used observation techniques, literature studies and interviews. Data analysis technique used is qualitative descriptive analysis technique. From the results of the research through observation and interviews with respondents are typical Palembang carving entrepreneurs in the area of Palembang carving industry is maintaining its business by: 1. entrepreneurs manage their finances through loan funds and also the benefits gained, reduce expenses that are not so necessary, and prioritize producing goods ordered besutan order goods that have been given a down payment. 2. Provide a low offer price but still no loss. 3. Reduce the employee so that they can still be given the appropriate wage with the work of their workers. 4. attend training for woodcarving artisans. While factors affecting the survival of typical carving business Palembang described to be a supporting factor and inhibiting factors. The hope for the future of this carving industry entrepreneurs hope the government can promote the typical carvings of Palembang not only in Palembang city but also outside the city of Palembang thus the craftsmen can leih diligent memproduksikan, also expected the government can provide loans without collateral and with a small interest for craftsmen can be bolder in taking orders in large quantities. And provide counseling and training for the craftsmen.